Therapeutic potential of allogeneic mesenchymal stromal cells transplantation for lupus nephritis. (November 2018) - Barbado, J; Tabera, S; Sánchez, A; García-Sancho, J
Animal and human studies have suggested the potential of mesenchymal stromal cells (MSCs) to treat systemic lupus erythematosus (SLE). Here, we present the results of compassionate MSC treatments for three SLE patients to provide the proof of concept for a randomized and controlled clinical trial. Three patients of different ethnicities who suffer from chronic SLE, and who presented with class IV active proliferative nephritis confirmed by biopsy, were treated with allogeneic MSCs from healthy donors. Ninety million cells were infused intravenously into each patient during high and very high activity disease flare-ups and follow-up was continued for 9 months. Multi-organic affectation was quantified by the SLE disease activity index (SLEDAI), and indicators of lupus nephritis activity, such as proteinuria, as well as lymphocyte and monocyte antigens and anti-HLA antibodies were measured at 1, 3, 6, and 9 months after treatment. Proteinuria levels improved dramatically during the 1st month after treatment and the ameliorations were sustained throughout the follow-up period. SLEDAI scores revealed early, durable, and substantial remissions that were complete for two patients and partial for the third patient and that permitted medication doses to be reduced 50–90%. These favourable outcomes support completion of the randomized and controlled MSC trial for SLE.